Research and design of a novel current mode charge pump - 李先锐 来新泉 李玉山 叶强 (Journal of semiconductors, 2009)
To meet the demands for a number of LEDs,a novel charge pump circuit with current mode control is proposed.Regulation is achieved by operating the current mirrors and the output current of the operational transconductance amplifier.In the steady state,the input current from power voltage retains constant,so reducing the noise induced on the input voltage source and improving the output voltage ripple.The charge pump small-signal model is used to describe the device’s dynamic behavior and stability.Analytical predictions were verified by Hspice simulation and testing.Load driving is up to 800 mA with a power voltage of 3.6 V,and the output voltage ripple is less than 45 mV.The output response time is less than 8μs,and the load current jumps from 400 to 800 mA.